2006
DOI: 10.1093/jb/mvj197
|View full text |Cite
|
Sign up to set email alerts
|

Prothymosin α Interacts with Free Core Histones in the Nucleus of Dividing Cells

Abstract: The acidic protein prothymosin alpha (ProTalpha), with a broad presence in mammalian cells, has been widely considered to have a role in cell division, through an unrevealed mechanism in which histones may be involved in view of their ability to interact with ProTalpha in vitro. Results of co-immunoprecipitation experiments presented here demonstrate that ProTalpha interacts in vivo with core histones in proliferating B-lymphocytes (NC-37 cells). This interaction occurs with histones H3, H2A, H2B and H4 locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 48 publications
1
13
0
1
Order By: Relevance
“…Other studies have implicated acidic peptides in transcriptional regulation (17,18). One of them, prothymosin ␣, has been found to interact with free his-FIGURE 5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have implicated acidic peptides in transcriptional regulation (17,18). One of them, prothymosin ␣, has been found to interact with free his-FIGURE 5.…”
Section: Discussionmentioning
confidence: 99%
“…tone proteins (18) and to modulate the interaction of histone H1 with chromatin (32). To study how C-peptide can stimulate rDNA transcription, we first investigated whether C-peptide interacts with histone extracts and observed that it had sequence-specific interactions with predominantly H4, but also H2B and S 18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to being a structural component of chromatin, histone H2AFX also maintains genomic stability and act as a multifunctional molecule [30] . The core histones form a nuclear multiprotein complex along with acetyltransferases, methyltransferases, hnRNPs, DNA helicase II, β-actin and vimentin, which may be associated with the structural modification of histones [31] . In addition,…”
Section: Pcbp1 Sat H2afx Fos Fst Tp53 Map2k2 Andmentioning
confidence: 99%
“…It has an unusual primary structure but lacks secondary structure (13). Although its function is still not well understood, current data suggest that ProT␣ facilitates cell proliferation and survival (14), remodeling of chromatin (15), and transcription (16). Previous in vitro studies have shown that ProT␣ is capable of preventing apoptotic cell death by inhibiting the formation of the apoptosome, a large cytosolic macromolecular complex formed in cells committed to programmed death (10).…”
mentioning
confidence: 99%